Dynamics of accessibility of medicines for type 2 diabetes monotherapy in Ukraine - T. A. Germanyuk; T. I. Ivko; V. P. Bobruk (The State Expert Center of the Ministry of Health of Ukraine, 2018)
Diabetes mellitus is recognized as noninfectious epidemic in the world. Antidiabetic medications for the patients are taking continually and they are expensive. So, the actual question is the evaluation of the economic availability of antidiabetic treatment. Compared with other similar researches the economic availability of monotherapy of type 2 diabetes mellitus in Ukraine has not been investigated. It was researched in this study. The purpose of the research was scientific generalization of the results of study of the economic availability of monotherapy of type 2 diabetes mellitus in Ukraine from 2013 to 2016. The material of the study were: ATC/DDD-indexes of Centre WHO methodology of statistical studies of drugs, cost of DDDs was calculated according to weighed average cost in November 2013 and November 2016, according to weekly «Pharmacy» information. Methods: frequency analysis, ATC/DDD-methodology, the calculation of socio-economic coefficients of accessibility: liquidity ratio (Cliq), solvency adequacy ratio (Ca.s.), availability ratio (D). Based on the results of our previous studies to analyze the dynamics of socio-economic accessibility have been selected schemes of monotherapy with metformin, gliclazide and glimepiride, as the most commonly used in clinical practice. It has been found that the minimum price for DDD of metformin increased by 101%, for glimepiride - by 65%, for gliclazide - by 41% from 2013 to 2016. In the study of liquidity ratio Cliq, it has been found that there was an increase of price fluctuations from 48 to 295%. In the study of the solvency adequacy ratio Ca.s., it has been found that the accessibility has decreased from 98 to 197%, respectively. In studying of availability ratio D it has been found that the growth rate of salary was lower rates therapy price increases by 67% for metformin, by 44% for glimepiride, by 5% for gliclazide. In the study of economic availability it has been found an increase in prices in 1.4 times for metformin, in 1.25 times - for glimepiride, in 4.3 times - for gliclazide. Accessibility of monotherapy of type 2 diabetes mellitus has been decreased by 98-197%. The rate of wage growth was less than the growth rate of prices for the medications under investigation by 5-67%. The obtained results of a study of the socio-economic accessibility of medicines for type 2 diabetes monotherapy for the population of Ukraine Cliq, Ca.s., D against the background of reducing the rate of salary growth show a decrease in the dynamics of such availability in the period 2013-2016 years.